The enrichment of the gut microbiota Lachnoclostridium is associated with the presence of intratumoral tertiary lymphoid structures in hepatocellular carcinoma - Zhao, Rui; Li, Jiacheng; Chen, Bo; Zhao, Jungang; Hu, Leyin; Huang, Kate; Chen, Qiwen; Yao, Jiangqiao; Lin, Ganglian; Bao, Lishimeng; Lu, Mengmeng; Wang, Yi; et al. (Frontiers in Immunology, 2023)
Backgrounds & Aimes: Immunotherapies have formed an entirely new treatment paradigm for hepatocellular carcinoma (HCC). Tertiary lymphoid structure (TLS) have been associated with good response to immunotherapy in most solid tumors. Nonetheless, the role of TLS in human HCC remains controversial and recent studies suggest their functional heterogeneity may relate to different locations within the tumor. Exploring factors that influence the formation of TLS in HCC may provide more useful insights. However, factors affecting the presence of TLSs are still unclear. The human gut microbiota can regulate the host immune system and is associated with the efficacy of immunotherapy, but in HCC, whether the gut microbiota is related to the presence of TLS still lacks sufficient evidence. Methods: We performed pathological examinations of tumor and para-tumor tissue sections. Based on the location of TLS in tissues, all patients were divided into intratumoral TLS (It-TLS) group and desertic TLS (De-TLS) group. According to the grouping results, we statistically analyzed the clinical, biological and pathological features, preoperative gut microbiota data and postoperative pathological features of patients. Results: In a retrospective study cohort of 60 cases from a single center, Differential microbiota analysis showed that compared with the De-TLS group, the abundance of Lachnoclostridium, Hungatella, Blautia, Fusobacterium and Clostridium was increased in the It-TLS group. Among them, the enrichment of Lachnoclostridium was the most significant and was unrelated to the clinical, biological and pathological features of the patients. It can be seen that the difference in abundance levels of microbiota is related to the presence of TLS. Conclusions: Our findings prove the enrichment of Lachnoclostridium-dominated gut microbiota is associated with the presence of intratumoral TLS in HCC patients.